H HUBUNGAN BODYSHAMING DENGAN KONSEP DIRI REMAJA DIPONDOK PESANTREN DARUL HIJRAH PUTRI MARTAPURA - Muhammad Anwari; Annisa Hafizah (LPPM Universitas Sari Mulia, 2020)
Background: mocking or critical comments about their body shape or size while self-concept is the whole picture of self, which includes a person's perception of himself, feelings, beliefs and values related to himself. Adolescence is a period that is most influenced by the environment and peers, it is the factors that influence the formation of personality, attitudes to self-concept which is an important aspect in adolescents. The existence of interactions to the search for self-identity in adolescents, of course, will find negative or unwanted things. For example, from peers, who commit acts of intimidation to harm adolescents, of course it will affect the development process.Objective: This study is to determine the relationship with self-concept in adolescents at Pondok Pesantren Darul Hijrah Putri Martapura.Methods: This research design uses Cross Sectional and uses the Pearson Product Moment statistical test. Sample was determined by Simple Random Sampling technique as many as 157 people out of 258 people.Results: The results of statistical analysis of the relationship between body shaming and self-concept obtained a correlation value of 0.657, meaning that the two variables have a strong relationship.Conclusion: There is a relationship between body shaming and self-concept in adolescents at the Senior High School of Darul Hijrah Pesantren Putri Martapura in 2020.